A steganography system and implementation utilising pseudo random number embedding and dynamic image production with graphs. (2015) - Aguilar, Ruben; Han, Jianchao
This paper proposes a new steganographic system that matches the image to the message by generating coherent noise. We utilise graphs as a means to organise the coherent noise over the message. Previous steganography methodologies are reviewed. The implementation of the proposed new system, RandSteg, is presented. The algorithms employed in the implementation system are discussed. Finally, further possibilities for research on this field are suggested.